Association between autism spectrum disorder and elevated DMFT index scores in children - Ibrahim, Sukaeni; Hardjo, Marsuki; Hardjo, Marhaen (Edelweiss Applied Science and Technology, 2025)
Children with Autism Spectrum Disorder (ASD) are known to be more susceptible to oral disease, with a higher DMFT (decayed, missing, filled teeth) index score compared to their typically developing peers. This is due to limited access to dental care services, involvement in self-injurious behaviors, and the adoption of dietary patterns that cause tooth decay. This study aims to consolidate academic knowledge through a systematic review identifying studies that compared children with autism to healthy control groups and examining the association between DMFT index scores and ASD by searching four representative literature databases (PubMed, Web of Science, Scopus, and Google Scholar) for publications spanning the years 2004 to 2024. Following the PRISMA checklist, a total of fourteen case-control studies met the inclusion criteria. The majority of these studies reported that children with ASD tend to have higher DMFT index scores compared to healthy controls. The findings of this study suggest that ASD is associated with a higher DMFT index score, indicating a potential increased risk of dental caries and oral health problems in children and adolescents with autism spectrum disorders. Further research is needed to elucidate the underlying mechanisms and identify effective interventions to improve dental health outcomes in this population.